What do academics know and do about plagiarism? An interview study with Chinese university teachers of English. Issue 6 (17th August 2020) - Sun, Xiaoya; Hu, Guangwei
Abstract : Previous research on plagiarism has increased awareness and knowledge of the various aspects of this issue, such as contributing factors to plagiarism, students' and teachers' perceptions of plagiarism, and institutional policies and regulations on plagiarism. Yet much of this research, especially on the latter two aspects, has been conducted in Anglo-American contexts or English-as-a-second-language (ESL) settings (where English is an official or important language in the larger societal context), while the diversity of English-as-a-foreign-language (EFL) contexts (where English as a foreign language is largely used only in the language classroom) remains relatively under-researched. Of those studies that did focus on EFL contexts, the majority were based on survey data that were limited in the depth of information collected. To address this relative lack of in-depth understanding of how plagiarism is understood and acted against in EFL contexts, this paper reports on an interview study with 13 EFL teachers from 12 universities in mainland China. The study focused on the teachers' knowledge and attitudes concerning plagiarism, plagiarism-related pedagogical practices, as well as perceived stances and expectations of their institutions in plagiarism prevention. Its findings contribute to the current knowledge base of EFL academics' views and practices regarding plagiarism, add to our understanding of EFL teachers' experiences concerning plagiarism in specific educational settings, and inform institutions' efforts to develop and improve strategies and policies for preventing plagiarism.